Comprehensive correlation for the prediction of the heat transfer through a single droplet in dropwise condensation regime. (5th June 2022) - Lethuillier, Jérémie; Miscevic, Marc; Lavieille, Pascal; Blanco, Stéphane; Coustet, Christophe; Topin, Frédéric
Abstract: Numerical simulations have been performed to determine the conduction heat transfer in a sessile droplet for a large range of dynamic contact angle θ and Biot number B i . The substrate is set at a constant and uniform temperature, while a convective heat transfer is set at the liquid–vapor interface. In such a configuration, the heat flux is concentrated in the triple line region, so that numerical results can become inaccurate as the Biot number increases. A reference case in which the heat flux can be determined analytically has thus be established to derive an empirical criterion on the local mesh refining needed to obtain accurate numerical results. To consolidate the results obtained with a finite elements code, calculations have been performed with a completely independent tool using Monte Carlo method on a set of cases. A correlation has then been derived from the numerical results data with a maximum deviation of less than 4% in the considered range of θ and B i, that covers conditions encountered in all the studies dealing with dropwise condensation of pure vapor. Comparisons with other laws available in literature have then been performed, evidencing some important discrepancies. Graphical abstract: Highlights: Available correlations lead to huge discrepancies when they are compared to each other. Elements of the mesh must be smaller than the inverse of the local Biot number. An unbiased correlation is provided to calculate the conduction thermal resistance. In dropwise condensation this law is valid whatever the Biot number and contact angle.